The venture capital state : the Silicon Valley model in East Asia - Klingler-Vidra, Robyn (Book collections on Project MUSE., 2018)
"Explores how the diffusion of the Silicon Valley venture capital policy model resulted in distinct, and effective, policies in Hong Kong, Taiwan and Singapore"--